2014
DOI: 10.1002/2013ja019154
|View full text |Cite
|
Sign up to set email alerts
|

Geo‐effectiveness and radial dependence of magnetic cloud erosion by magnetic reconnection

Abstract: [1] Magnetic flux erosion by magnetic reconnection occurs at the front of at least some magnetic clouds (MCs). We first investigate how erosion influences the geo-effectiveness of MCs in a general sense and using a south-north magnetic polarity MC observed on 18-20 October 1995. Although the magnetic shear at its front may not be known during propagation, measurements at 1 AU show signatures of local reconnection. Using a standard MC model, an empirical model of the geomagnetic response (Dst), and an observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 67 publications
(126 reference statements)
4
55
0
Order By: Relevance
“…In this location out‐of‐ecliptic magnetic fields and planar structures are likely to result from the draping of magnetic field lines around the magnetic ejecta [ McComas et al , ], and we discussed a specific example of these. Sometimes, these draped fields may also be consistent with eroded CME fields as proposed in Lavraud et al [].…”
Section: Discussionsupporting
confidence: 79%
“…In this location out‐of‐ecliptic magnetic fields and planar structures are likely to result from the draping of magnetic field lines around the magnetic ejecta [ McComas et al , ], and we discussed a specific example of these. Sometimes, these draped fields may also be consistent with eroded CME fields as proposed in Lavraud et al [].…”
Section: Discussionsupporting
confidence: 79%
“…A similar tail was found with the 18-20 October 1995 ICME, where the remaining magnetic field is interpreted as a partially reconnected flux rope by Dasso et al (2006). Ruffenach et al (2012) and Lavraud et al (2014) closely examined several ICME events and found evidence (including reconnection jets) that magnetic reconnection occurred on the front side of the MC flux ropes, leading to their erosion. Ruffenach et al (2012) (Lepping and Wu 2007).…”
Section: Flux Rope Erosionsupporting
confidence: 66%
“…The analyses of MCs in many studies (e.g., Chané et al 2005;Dasso et al 2006Dasso et al , 2007Ruffenach et al 2012Ruffenach et al , 2015Lavraud et al 2013Lavraud et al , 2014 have revealed the predicted features of flux rope erosion. Dasso et al (2006) examined the 21 January 2005 ICME and found a large imbalance in B z that they attribute to magnetic reconnection.…”
Section: Flux Rope Erosionmentioning
confidence: 99%
“…The speed, density, pressure, magnetic field, and shock structure can all change as the ICME expands and interacts both with the ambient solar wind as well as with various disturbances within it. In particular, through observational and modeling work, studies have shown that during propagation the flux rope may kink and deform [ Manchester et al , ], reconnection/erosion of internal ICME magnetic flux may occur [ Lavraud et al , ; Ruffenach et al , ], and the ICME may also get deflected [ Manchester et al , ; Kay et al , , ; Wang et al , ] and rotated [ Kliem et al , ; Lynch et al , ]. A recent CME event study by Nieves‐Chinchilla et al [] using both in situ and remote sensing observations from STEREO, SOHO, MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER), and Wind showed evidence for significant reorientation of the flux rope axis.…”
Section: Introductionmentioning
confidence: 99%